Conocimiento y actitud hacia la lista de verificación de la cirugía segura en enfermeros de los servicios asistenciales del Hospital Regional de Loreto Iquitos 2023 - Pilco Escalante, Valery (2024)
The main objective was to determine the relationship between knowledge and attitude towards the Safe Surgery checklist in nurses from the care services of the Regional Hospital of Loreto 2023. The quantitative method was used with a non-experimental, descriptive, correlational design. cross section. The population and sample were made up of 80 nurses from the Emergency, Surgery, Surgical Center, Pediatrics, Gynecology and Maternity services of the Loreto Regional Hospital. The technique used was the survey and the instruments were the knowledge questionnaire on the Safe Surgery Checklist and the Safe Surgery attitude scale. The information was processed using descriptive statistics through the statistical package SPSS version 24.0. For the bivariate analysis, the non-parametric inferential statistics of free distribution called Chi Square (X2) was used, the level of significance was α 0.05. The results obtained were: regarding the level of knowledge of the safe checklist in nurses from HRL care services, 45.0% reached a medium level, 72.5% showed a favorable attitude. The work concludes that: There is an association between the level of knowledge and attitude towards the safe surgery checklist in nurses in the care services of the Loreto Regional Hospital, Kendall's Tau-b coefficient of 0.302 and approximate significance of 0.003 (p < 0 .05).